PEMBIAYAAN INDUSTRI KEÇIL PADA PERKAMPUNGAN INDUSTRI KECIL (PIK) PENGGILINGAN PULO GĄDUNG - Safnita Safnita (Media Riset Bisnis & Manajemen, 2003)
Smallindustries in Indonesia have an important involvementin the economy, but qualitatively its development is facing some problems especially in the avaibility of capital. This research is done to find out the influences of the Bank Loan to the development of small industry. This research analyzes performance of small industries activities. It includes the production, selling, labours, labours skil, and profit. The result shows the development of small industries before and after the giving of Bank Loan. The test was done using proportion and paired sample test Base on the data of Small Industry Village (PIK) in Pulo Gadung, 68.6% is clothes industry and 31.4% is leather shoes and bag industry. The research shows that most small industry at Small Industry Vilage (PIK) in Puto Gadung operate their industry by using their own capital the involvement of Bank Loan is very low.